2022
DOI: 10.1038/s41467-022-33324-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell cycle state determines propensity for arterial-venous fate

Abstract: During blood vessel development, endothelial cells become specified toward arterial or venous fates to generate a circulatory network that provides nutrients and oxygen to, and removes metabolic waste from, all tissues. Arterial-venous specification occurs in conjunction with suppression of endothelial cell cycle progression; however, the mechanistic role of cell cycle state is unknown. Herein, using Cdh5-CreERT2;R26FUCCI2aR reporter mice, we find that venous endothelial cells are enriched for the FUCCI-Negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 80 publications
6
35
0
Order By: Relevance
“…S9 C and D). Recent work suggests that arterial ECs under high FSS are in late G1 arrest (31), suggesting activation of CDK4 or CDK2. Flavopiripol targets these isoforms, though it also inhibits CDK9 (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9 C and D). Recent work suggests that arterial ECs under high FSS are in late G1 arrest (31), suggesting activation of CDK4 or CDK2. Flavopiripol targets these isoforms, though it also inhibits CDK9 (32).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest a connection between artery remodeling and the cell cycle. Recent work has shown that arterial specification, which is associated with high FSS, requires cell cycle arrest, specifically in late G1 (31). Physiological FSS is well known to induce cell cycle arrest, though the specific phase has not been explored (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation and migration are integral to angiogenesis. 58,59 Proangiogenic stimuli, like VEGF and hypoxia, increased FAM222A mRNA and protein levels while silencing FAM222A decreased VEGF-induced EC migration, proliferation, vascular spouting in vitro, ex vivo, and in Matrigel plug revascularization in vivo (Figure 1H and 1N, 2A through 2G); FAM222A overexpression had opposite effects. FAM222A silencing did not alter activation of p53 or p53-mediated p21 (data not shown) nor induce apoptosis, excluding these as explanations for decreased cell proliferation and migration after FAM222A silencing.…”
Section: Discussionmentioning
confidence: 98%
“…In these vascular beds, Dll4-Notch signaling interactions at the sprouting front induces an endothelial fate switch and specifies future arterial cells among the tip cell progeny (Fang et al, 2017; Hasan et al, 2017; Hou et al, 2022; Pitulescu et al, 2017; Xu et al, 2014). More recent evidence points to a priming mechanism of tip cells towards an arterial fate that is linked to the Notch pathway directly inducing metabolic and cell cycle arrest (Chavkin et al, 2022; Fang et al, 2017; Luo et al, 2021; Su et al, 2018) and subsequently more responsiveness to migratory cues (Hasan et al, 2017; Luo et al, 2021; Pitulescu et al, 2017). The Cxcl12-Cxcr4 chemokine signaling axis has been identified as a critical downstream target of Notch in this process (Hasan et al, 2017; Luo et al, 2021; Pitulescu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%